Study on the failure process and nonlinear safety of high arch dam and foundation based on geomechanical model test. (October 2020) - Wang, Xingwang; Liu, Yaoru; Tao, Zhuofu; Wang, Weiqiang; Yang, Qiang
Highlights: Failure process is obtained through geomechanical model test with overload method. A method for determining the nonlinear safety factor of arch dam is proposed. The method is based on the Pearson product-moment correlation coefficient. The failure mode of arch dam is more dominated by foundation. The nonlinear deformation safety factor is similar with compressive stress safety. Abstract: The nonlinear safety is very important for the system of arch dam and its foundation since it is statically indeterminate structure and the geomechanical model test is effective method to evaluate the stability of arch dam. The analysis of failure process for a double-curvature arch dam with 167.5-meter-high, located in the northwest of China, has been carried out based on overload method. A quantitative method for determining the safety factor of initial nonlinear deformation of model test is proposed based on the Pearson product-moment correlation coefficient. Through the defromation evolution of all monitoring points, the nolinear safety has been determined. Then it is verified by acoustic emission data. By comparing the model test results of arch dam with other arch dams, the overall stability and safety of narrow valley arch dam is higher, and its failure mode is more dominated by foundation, while that of wide valley arch dam is more dominated by dam. The safety factor of initial nonlinear deformation, which has the same meaning as the control index of compressive stress safety of arch dam in the design specification, correspond to the compressive stress failure of the downstream dam toe.